In-patient satisfaction with nurse caring in Southeast Sulawesi Provincial Hospital - La Rangki; Ulfa Dayanti; A Asriati (Universitas Aisyah Pringsewu, 2019)
The nurse has the most important role in the health sector. In providing nursing care, nurses must have a caring attitude, because caring includes relationships between humans and influences on service quality and patient satisfaction. This research aim to know Relationship of caring behavior of nurses with patient satisfaction in the Laika Waraka Non Surgical In patient Room at the Bahteramas General Hospital Of Southeast Sulawesi Province. This research was an analytic observational study with cross sectional approach. Sampling technique is done by accidental sampling as many as 67 respondents. The results of the study using the chi square test. Respondents who argued that nurses caring behavior was enough amounted to 44 respondents (65,6%) and respondents who exppressed satisfaction with health services amounted to 47 (70,1%).Thus, there is relationship of caring behavior of nurses with patients satisfied in the Laika Waraka non surgical inpatient room at Bahteramas General Hospital Of Southeast Sulawesi Province. Suggestion for nurses to cultivate caring behavior in the provision of daily services in particular more timely in providing services so that to improve the quality of hospital service, particularly in nursing care field.AbstrakPerawat memiliki peran paling utama dalam bidang kesehatan. Dalam memberikan asuhan keperawatan, perawat harus memiliki sikap caring, karena caring mencakup hubungan antar manusia dan berpengaruh terhadap mutu pelayanan dan kepuasan pasien. Penelitian ini bertujuan untuk mengetahui hubungan perilaku caring perawat dengan kepuasan pasien di Ruang Rawat Inap Laika Waraka Non Bedah Rumah Sakit Umum Daerah Bahteramas Provinsi Sulawesi Tenggara. Desain penelitian ini adalah analitik observasional study dengan pendekatan cross sectional. Teknik pengambilan sampel dilakukan dengan aksidental sampling dengan jumlah total responden sebanyak 67 responden.Hasil penelitian menggunakan uji statistik chi square, diperoleh data yakni perilaku caring perawat dengan kategori cukup berjumlah 44 responden (65,6%), dan responden yang mengatakan puas terhadap pelayanan kesehatan berjumlah 47 responden (70,1%), artinya ada Hubungan Perilaku Caring Perawat dengan Kepuasan Pasien di Ruang Rawat Inap Laika Waraka Non Bedah RSUD Bahteramas Provinsi Sulawesi Tenggara. Saran bagi perawat agar membudayakan perilaku caring dalam pemberian pelayanan sehari-hari khususnya lebih tepat waktu dalam memberikan pelayanan sehingga dapat meningkatkan mutu pelayanan Rumah sakit khususnya dibidang pelayanan keperawatan.